Left atrial appendage clot with severe mitral stenosis, responders and non-responders with anticoagulation, a prospective cohort study. - Tariq Ashraf; Kanwal Fatima Aamir; Asif Nadeem; Shirjeel Murtaza; Parveen Akhtar; Samra Yasmin; Rahmat Ghaffar; Mahmood ul Hassan; Fateh Ali Tipoo (International Journal of Endorsing Health Science Research, 2022)
Background: One of the most frequently observed valvular heart lesions is Mitral stenosis (MS), characterized by left ventricular inflow tract obstruction at the mitral valve level caused by different etiologies. Early detection of symptomatic mitral stenosis with a thrombus in LAA, not responding to anticoagulation in due course of time are sent for Mitral valve replacement rather than undergoing PTMC. The current study aims to see the anticoagulation response in different types of left atrial appendages so that non-responders can be referred for surgery on the first TEE and Cardiac CT. Methodology: The current study will observe the frequency of left atrial appendage (LAA) thrombus resolution after three months of anticoagulation in patients with severe MS. It will assess the response rate in different morphologies of LAA so that non-responders can be referred for surgery on the very first TEE and Cardiac CT. Consecutive MS patients with thrombus in LAA detected via transesophageal echocardiography will be included in the study. According to the standard procedure, TEE followed by Cardiac CT will be performed after obtaining informed consent from the patients. Discussion: Detecting the anticoagulation response using follow-up TEE in different types of left atrial appendages might be helpful for the non-responders that can be referred for surgery after TEE and Cardiac CT on first examination and TEE only at the end of three months. Trial registration number: The trial was registered on ClinicalTrials.gov (NCT05186649).